The perceived impact of security and privacy risks on social commerce amongst social media users in South Africa - Ramjith, Samresh (University of the Witwatersrand, Johannesburg, 2023)
This research investigated the influence of social media attitude, social media trust, and risk awareness (cybersecurity and privacy) on social commerce intention. Five hypotheses were proposed, which were then tested with a sample of social media users via an online survey. Survey results were cleaned and then analysed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The study did not find a significant direct effect of social media attitude on social commerce intention, but did find that social media attitude was found to significantly influence social media trust. The moderation effects of cybersecurity risk awareness and privacy risk awareness on the relationship between social media trust and social commerce intention were not supported. The study supports and reinforces the importance of trust in social commerce and the need for businesses and social media platforms to continuously work to enhance trust amongst users. A research outcome is the necessity for deeper investigation into the role of user attitudes and risk awareness in social commerce. The study contributes to the social commerce literature by providing empirical evidence about the complex interplay between trust, attitude, and risk awareness, contributing to enhancing understanding of these relationships and their impact on business strategies
A research proposal submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business Johannesburg, 2023
Keywords: Cyber security; privacy; Awareness; South Africa; Social commerce; Digital commerce; Cybercrime; PLS SEM; UCTD; SDG-9: Industry, innovation and infrastructure